Kontinuitas Narasi Mitologi Garuda Dalam Wonderland Indonesia I dan II Karya Alffy Rev - Ahmad Toni (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
This research is about Wonderland Indonesia 1 and 2videos which focus on the continuity of the narrative on the sign in the video. The method used in this research is narrative analysis which is formulated on five narrative elements. The results of the study illustrate, the equilibrium narrative is indicated by the dark world of Antaboga, the distruption narrative is indicated by the emergence of Garuda and Surya Majapahit as the world of awakening, the recognition distruption narrative is indicated by the apprearance of Dewi Winata as a description of the world of consciousness, the attempt to repair the distruption narrative is indicated by the trident as an illustration of the creation, maintenance and dissolution of the universe, the reinstatement of the equilibrium narrative is marked by Garuda as a decipction of the story freedom and independence.